HISTORICAL SOCIAL MOVEMENTS IN SALVADOR AND BAHIA IN THE LONG DURATION - Vasconcelos, Pedro de Almeida (Mercator; Vol 22 (2023), 2023)
The text deals with the social movements that took place in Salvador and in the captaincy/province/state of Bahia, in the long duration from 1500/1549 to the present day, based on the results of research carried out for my book Salvador: transformações e permanências and other materials most recent. The text is divided into four parts. Initially, a review was carried out on the literature of social movements in sociology and geography. Then, in view of the long duration, social movements in Salvador were divided into Colony, Empire and Republic. The notion of social movements was used in that book as one of the transforming agents of the city. KEY-WORDS    Social movements; Salvador; Bahia;